Culture from the slums : punk rock in East and West Germany - Hayton, Jeff (Oxford University Press, 2022)
Culture from the Slums explores the history of punk rock in East and West Germany during the 1970s and 1980s. These decades witnessed an explosion of alternative culture across divided Germany, and punk was a critical constituent of this movement. For young Germans at the time, punk appealed to those gravitating towards cultural experimentation rooted in notions of authenticity-endeavors considered to be more 'real' and 'genuine.' Adopting musical subculture from abroad and rearticulating the genre locally, punk gave individuals uncomfortable with their societies the opportunity to create alternative worlds. Examining how youths mobilized music to build alternative communities and identities during the Cold War, Culture from the Slums details how punk became the site of historical change during this era: in the West, concerning national identity, commercialism, and politicization; while in the East, over repression, resistance, and collaboration. But on either side of the Iron Curtain, punks' struggles for individuality and independence forced their societies to come to terms with their political, social, and aesthetic challenges, confrontations which pluralized both states, a surprising similarity connecting democratic, capitalist West Germany with socialist, authoritarian East Germany. In this manner, Culture from the Slums suggests that the ideas, practices, and communities which youths called into being transformed both German societies along more diverse and ultimately democratic lines. Using a wealth of previously untapped archival documentation, this study reorients German and European history during this period by integrating alternative culture and music subculture into broader narratives of postwar inquiry and explains how punk rock shaped divided Germany in the 1970s and 1980s.